Propuesta de mejoras para procesos y servicios del departamento tics del Hospital Isidro Ayora basado en estándares de calidad Cobit 4.1 e Itil v3. - Morocho Arévalo, Dunnia Paola (2016)
Today, it is vital that institutions, whether public or private, offer services or processes of high quality, in such a way that they generate satisfaction and wellbeing in the end user. This project aims to improve the quality and efficiency of the sequence of activities that form a process. To achieve this, a plan was created to improve the processes and services offered within the ICT Department of the Isidro Ayora Hospital in the city of Loja, which seeks to take advantage of the existing resources. For the implementation of the Project, the Six Sigma methodology was used, which consists of 5 phases: define, measure, analyze, improve and control. From the second phase of the methodology, the project was complemented by the guidelines set out in the ITIL and COBIT 4.1 v3 standards, which define a set of good practices for the control of the ICT resources and activities. Additionally, techniques such as interviews and surveys were used for the collection of information, from which the most relevant information for the proposed purposes was extracted. In this way, the proposed improvement plan was constructed and, together with the head of the ICT department, corrective actions was applied to two previously selected processes whose results reflected the implementation and effectiveness of the outlined measures; thereby satisfying the overall objective of the present project.